The correlation of tool wear parameters with machining process parameters - Kovač, Pavel; Savković, Borislav; Rodić, Dragan; Ješić, Dušan (Journal of Production Engineering, 2023)
<div class="min-h-[20px] text-message flex flex-col items-start gap-3 whitespace-pre-wrap break-words [.text-message+&]:mt-5 overflow-x-auto" data-message-author-role="assistant" data-message-id="b30e927b-0267-403e-9701-10437c3c59ab"> The paper delineates correlations established between tool wear parameters and the machinability parameters in face milling processes: cutting temperature, cutting forces, and surface roughness, as per concurrent measurements. The systematic arrangement of measurements facilitated the simultaneous tracking of the progress of all scrutinized parameters concerning cutting time until tool wear occurred under specific cutting conditions. This organized approach allowed for the modeling of correlations among these parameters, aiding in understanding their interdependencies and effects on the machining process.